Expedited retrieval of high-quality Usutu virus genomes via Nanopore sequencing with and without target enrichment - Holicki, Cora M.; Bergmann, Felicitas; Stoek, Franziska; Schulz, Ansgar; Groschup, Martin H.; Ziegler, Ute; Sadeghi, Balal (Frontiers in Microbiology, 2022)
Usutu virus (USUV) is a mosquito-borne zoonotic virus and one of the causes of flavivirus encephalitis in birds and occasionally in humans. USUV rapidly disperses in a susceptible host and vector environment, as is the case in South and Central Europe. However, compared to other flaviviruses USUV has received less research attention and there is therefore limited access to whole genome sequences and also to in depth phylogenetic und phylodynamic analyses. To ease future molecular studies, this study compares first- (partial sequencing via Sanger), second- (Illumina), and third-generation (MinION Nanopore) sequencing platforms for USUV. With emphasis on MinION Nanopore sequencing, a cDNA-direct and a target-enrichment (amplicon-based) sequencing approach were validated in parallel. The study was based on four samples from succumbed birds commonly collected throughout Germany. The samples were isolated from various sample matrices, organs as well as blood cruor, and included three different USUV lineages. We concluded that depending on the focus of a research project, amplicon-based MinION Nanopore sequencing can be an ideal cost- and time-effective alternative to Illumina in producing optimal genome coverage. It can be implemented for an array of lab- or field-based objectives, including among others: phylodynamic studies and the analysis of viral quasispecies.